Research on adsorption of Ni2+ ions using halloysite clay and the ability of desorption and nickel recovery by electrochemical method - Duyen, Le Thi; Thao, Le Thi Phuong; Dung, Cong Tien; Hung, Nguyen Viet; Hung, Ha Manh; Tien, Mai Van; Thao, Nguyen Thi Thanh; Bac, Bui Hoang (Vietnam Journal of Science and Technology, 2024)
Nickel is a useful metal, people’s demand for nickel is increasing while nickel mines are increasingly exhausted. It is essential to recover nickel from waste sources to avoid environmental pollution and to utilize it. In this work, we research on the ability adsorption of Ni2+ ions from aqueous solution using halloysite clay (HAL), which was taken from Thach Khoan area, Phu Tho, Vietnam then desorption of Ni2+ out of HAL and recovery of Ni metal. The light-yellow HAL powder had a specific surface area of 20.152 m2/g with particle sizes of approximately < 32 µm. Several factors affecting the Ni2+ adsorption property such as pH value, the contact time, the adsorbent dose and the initial concentration of Ni2+ ions were investigated in aqueous solution. The adsorption efficiency and capacity obtained under suitable conditions (0.8 g HAL per 50 mL solution, 50 mg/L of Ni2+ initial concentration, 80 minutes of contact time, pH0 of 5.9, and at room temperature of 30 oC) were 82.59 % and 2.58 mg/g, respectively. The results of adsorption stoichiometry of Ni2+ ions on the HAL adsorbent were fitted to the Langmuir adsorption isotherm model (R2 = 0.9931) with the maximum monolayer adsorption capacity of 3.739 mg/g. The adsorption process obeyed a pseudo-second-order kinetic model with R2 = 0.9911. Desorption of Ni2+ ions from loaded HAL material and recovery of Ni metal were conducted in a deep eutectic solvent based on choline chloride and urea (reline) by using electrodeposition method. The results showed that 92.65 % of the Ni metal could be recovered after 5 hours and applied current of 7.5 mA at 60 °C.